Solvothermal Synthesis of ZnO Nanoparticles for Photocatalytic Degradation of Methyl Orange and p-Nitrophenol - Ying Wang (MDPI AG, 2021)
The photocatalytic degradation of organic pollutants is an effective method of controlling environmental pollution. ZnO nanoparticles (ZnO NPs) were prepared by the solvothermal method and characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV–visible diffuse reflectance spectroscopy (UV–Vis DRS). The results showed that the ZnO NPs had a uniform size of 25–40 nm, hexagonal wurtzite structure, and a band gap of 2.99 eV. The photocatalytic degradation of methyl orange (MO) and p-nitrophenol (PNP) was used as a model reaction to evaluate the photocatalytic activity of ZnO NPs. The photocatalytic degradation rates (pseudo-first-order kinetics) of MO and PNP were 92% (0.0128 min−1) and 56.2% (0.0042 min−1), respectively, with a 25 W ultraviolet lamp, MO/PNP concentration = 20 mg/L, ZnO NPs dose = 1.5 g/L, and time = 180 min. The photocatalytic mechanism of ZnO NPs and degradation pathways of MO and PNP were also proposed. The results provide valuable information and guidance for the treatment of wastewater via photocatalytic methods.